INTESTINE AND LIVER HISTOPATHOLOGY OF STRIPED CATFISH (Pangasianodon hypophthalmus) FEEDING CONTAINING PAPAYA LEAF FERMENTATION - Purba, Yoshua Dewaman Mangapul; Syawal, Henni; Lukistyowati, Iesje (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
Aeromonas hydrophila bacteria often attack internal organs such as the liver and intestines. This research was conducted in June – August 2021 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Universitas Riau. Histology preparations were made at the Bukittinggi Veterinary Center. This research aimed to obtain the best dose addition of papaya leaf fermented solution which could reduce intestinal and liver tissue damage of striped catfish (P.hypophthalmus) which was challenged with A.hydrophila. The method used is an experimental method with a completely randomized design (CRD) with 4 treatment levels and 3 replications; Kp (Feed not given papaya leaf fermented solution + infected with A.hydrophila), P1 (16 ml/kg feed of papaya leaf fermented solution + infected with A.hydrophila), P2 (16 ml/kg feed of papaya leaf fermented solution) + infected with A.hydrophila), P3 (16 ml/kg of papaya leaf fermented solution feed + infected with A. hydrophila). The fish used was 8-10 cm with a density of 1 fish/3 L totaling 10 fish with a container measuring 40x30x30 cm. Infection by injection in the intramuscular section as much as 0.1 mL/head with a bacterial density of 108 CFU/mL. The parameters observed were clinical symptoms for 72 hours and histopathology of the intestine and liver of striped catfish. The results showed that the intestine saw the presence of hemorrhage, necrosis, and edema. While the liver shows abnormalities, such as hemorrhage, necrosis, hypertrophy, and fatty degeneration.